Variable Presentations of Peripheral Exudative Hemorrhagic Chorioretinopathy - Alsakran, Wael A. (Middle East Afr J Ophthalmol, 2020)
Three cases of peripheral exudative hemorrhagic chorioretinopathy (PEHCR), which mimicked other retinal pathologies, were reported. Different preliminary diagnoses were made initially, but thorough examination combined with the appropriate investigations led to the final diagnosis of PEHCR. Despite the rare occurrence of PEHCR, it must be included in the differential diagnosis for peripheral retinal diseases.